2015
DOI: 10.3340/jkns.2015.58.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Stand-Alone Polyetheretherketone Cage versus Zero-Profile Anchored Spacer in Single-Level Anterior Cervical Discectomy and Fusion : Minimum 2-Year Assessment of Radiographic and Clinical Outcome

Abstract: ObjectiveWe compared the clinical and radiographic outcomes of stand-alone polyetheretherketone (PEEK) cage and Zero-Profile anchored spacer (Zero-P) for single level anterior cervical discectomy and fusion (ACDF).MethodsWe retrospectively reviewed 121 patients who underwent single level ACDF within 2 years (Jan 2011-Jan 2013) in a single institute. Total 50 patients were included for the analysis who were evaluated more than 2-year follow-up. Twenty-nine patients were allocated to the cage group (m : f=19 : 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 27 publications
2
39
0
Order By: Relevance
“…They found fusion was achieved in 93.5% of patients after a median follow-up of 23 months. In the other 12 articles, the analysis was performed by a clinician, usually a neuro-or orthopaedic surgeon [12,29,35,61,67,69,87,92,96,[109][110][111]. They found fusion was achieved in 85.5% of patients after a median follow-up of 23 months.…”
Section: Methods Of Measuring Bony Fusionmentioning
confidence: 99%
“…They found fusion was achieved in 93.5% of patients after a median follow-up of 23 months. In the other 12 articles, the analysis was performed by a clinician, usually a neuro-or orthopaedic surgeon [12,29,35,61,67,69,87,92,96,[109][110][111]. They found fusion was achieved in 85.5% of patients after a median follow-up of 23 months.…”
Section: Methods Of Measuring Bony Fusionmentioning
confidence: 99%
“…Previously, Cho et al4) reported that the PEEK-titanium combined anchored cage showed a statistically better outcome in Cobb angle, disc height, subsidence rate than the stand-alone cage. Furthermore, Song et al24) reported that anterior cervical cage-plate is more beneficial with regard to postoperative results than the stand-alone cage.…”
Section: Discussionmentioning
confidence: 99%
“…A zero-profile device is thought as a valuable alternative for ACDF with a low incidence of postoperative dysphagia and without segmental kyphotic change (34). Cho et al found that the zero-profile anchored spacer has some advantage over stand-alone PEEK cage for maintaining segmental lordosis and lowering subsidence rate after single level ACDF (35). Barbagallo et al mentioned that SF-36 and NDI showed a statistically significant improvement and mean arm pain VAS score deterioration on zero-profile cage-plate device.…”
Section: Discussionmentioning
confidence: 99%